Por um cinema humanista: A identidade cinematográfica de Walter Salles,de a grande arte até abril despedaçado - Mariana Mol Goncalves (2007)
Walter Salles is one of the Brazilian directors whose cinematographicproduction is to regulate and well accepted by the public and the critics. National and internationally recognized, Salles had directed documentaries, among short and long-films, but over than a decade he dedicated himself to the fiction cinema - until the present year of 2007 he released nine films. The director believes that the form and the technique always must serve the narrative: his formal choices always refer to the histories that he wants to tell. Salles films evidence the re-education ofthe view; the migration and the exile; the search for a second chance and, mainly, the transformation through affection. The director considers himself as a documentarist that directs fiction and, not by a chance, has a strong documentary component in all his films. This study brings the analysis of five fiction long movies directed by Salles (High art, Foreign land, Central Station, Midnight and Behind the Sun) and a collection of elements that typifies the director cinematographic work and identify his way (and his strategies) of telling histories. Indirectly, this study also describes a recent period of the Brazilian cinema (the Retomada),through the directors view that desires to tell histories that takes the real,contemporary, and seen from the inside, Brazil. Salles concerns with a humanist cinema.